Visionary leadership and strategic management - Westley, Frances; Mintzberg, Henry (Strategic Management Journal, 1989)
This paper describes the concept of visionary leadership in a new way, more suitable for strategic management. First, drawing on an account of theatre, it presents a model of visionary leadership as drama, an interaction of repetition, representation, and assistance. Second, considering the experiences of a number of visionary leaders, in terms of style, process, content, and context, the paper describes various types of visionary leadership—the creator, the proselytizer, the idealist, the bricoleur, and the diviner.